Resistance of wheat genotypes to the greenbug Schizaphis graminum (Rondani, 1852) (Hom., Aphididae) - Tonet, Gabriela Lesche; da Silva, Rogério F. Pires (Pesquisa Agropecuaria Brasileira, 1995)
The reaction of wheat (Triticum aestivum L.) genotypes to the damages caused by Schizaphis graminum (Rondani, 1852) (Hom., Aphididae), when naturally infested in the field, was studied in 1988 and 1989. Trials were set up at the experimental area of EMBRAPA-CPAO, in Dourados, Mato Grosso do Sul, Brazil, using 14 lines and 25 cultivars of wheat. A randornized block design in factorial, with four replications, was used, being the plots with and without greenbugs and the wheat genotypes the subplots. Assessments were made by recording the damage level, number of spikes per meter, and grain yield. The line PF 86414 showed no reductions in grain yield evidencing its resistance to S. graminum. Sulino, PAT 7219, Ocepar 8. El Pato, Iapar 1, 131118, and BR 1 were the most suscetible cultivars to the greenbug.